Aberrant ocular architecture and function in patients with Klinefelter syndrome. Issue 1 (December 2017) - Brand, Cristin; Zitzmann, Michael; Eter, Nicole; Kliesch, Sabine; Wistuba, Joachim; Alnawaiseh, Maged; Heiduschka, Peter
Abstract Klinefelter Syndrome (KS), the most common chromosomal disorder in men (47, XXY), is associated with numerous comorbidities. Based on a number of isolated case reports, we performed the first systematic and comprehensive evaluation of eye health in KS patients with a focus on ocular structure and vascularization. Twenty-one KS patients and 26 male and 38 female controls underwent a variety of non-invasive examinations investigating ocular morphology (examination of retinal thickness, optic nerve head, and cornea) and function (visual field testing and quantification of ocular vessel density by optical coherence tomography angiography). In comparison to healthy controls, KS patients exhibited a smaller foveal avascular zone and a decreased retinal thickness due to a drastically thinner outer nuclear layer. The cornea of KS patients showed a decreased peripheral thickness and volume. In perimetry evaluation, KS patients required brighter stimuli and gave more irregular values. KS patients show an ocular phenotype including morphological and functional features, which is very likely caused by the supernumerary X chromosome. Thus, KS should not be limited to infertility, endocrine dysfunction, neurocognitive and psychosocial comorbidities. Defining an aberrant ocular morphology and function, awareness for possible eye problems should be raised.